Common Endpoints for Non-Commutative Suzuki Mappings: Thanomsak Laokul, Bancha Panyanak - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we prove an endpoint theorem for multi-valued Suzuki mappings in uniformly convex hyperbolic spaces. As a consequence, we obtaina common endpoint theorem for a pair of single-valued and multi-valued Suzuki mappings without the commutative condition. Our results extend and improve the results of Espinola et al. (2015), Saejung (2016), Kudtha and Panyanak (2018) and many others.